The future of leadership : today's top leadership thinkers speak to tomorrow's leaders - Bennis, Warren G.; Spreitzer, Gretchen M.; Cummings, Thomas G. (San Francisco : Jossey-Bass, 2001)
A collection of wisdom and inspirational offerings, from todays business leaders to those who would be leaders tomorrow. Topics range from the arrival of the era of human capital to creating a context for creativity in the workplace. Examines challenging issues tomorrow's leaders may face.
Preface / Thomas G. Cummings, Gretchen M. Spreitzer -- Part 1: Setting the stage for the future -- The future has no shelf life / Warren Bennis -- The era of human capital has finally arrived / Edward E. Lawler III -- Part 2: The organization of the future -- A world of fleas and elephants / Charles Handy -- Knowledge work and the future of management / Thomas H. Davenport -- Boundaryless / Steven Kerr -- Trust me on this: organizational support for trust in a world without hierarchies / Thomas A. Stewart -- Part 3: The leader of the future -- Bringing leadership lessons from the past into the future / James M. Kouzes, Barry Z. Posner -- Leadership as the legitimation of doubt / Karl E. Weick -- Leading yourself / Philip Slater -- The context of creativity / Mihaly Csikszentmihalyi -- Why do we tolerate bad leaders? Magnificent uncertitude, anxiety, and meaning / Jean Lipman-Blumen -- The evolving role of executive leadership / Cathy L. Greenberg-Walt, Alastair G. Robertson -- When leadership is an organizational trait / James O'Toole -- Part 4: How leaders stay on top of their game -- Just say yes! / Tom Peters -- Heroic leadership's greatest battle: the defeat of disappointment versus the disappointment of defeat / Jeffrey Sonnenfeld -- Part 5: Insights from young leaders -- Where the leaders are: the promise of youth leadership / Tara Church -- Seeking a newer world / Edward W. Headington -- Part 6: Some closing thoughts -- The leadership challenges of the next generation / Gretchen M. Spreitzer, Thomas G. Cummings -- Postlude: an intellectual memoir / Warren Bennis -- Notes and references -- Index -- The authors.
Includes bibliographical references (p. 281-292) and index.
Keywords: Leadership; Organizational effectiveness; Organizational change; Management